Super Mario Strikes Back: Another Molinist Reply to Welty’s Gunslingers Argument - McNabb, Tyler Dalton (Perichoresis, 2018)
Molinists generally see Calvinism as possessing certain liabilities from which Molinism is immune. For example, Molinists have traditionally rejected Calvinism, in part, because it allegedly makes God the author of sin. According to Molina, we ‘should not infer that He is in any way a cause of sin’. However, Greg Welty has recently argued by way of his Gunslingers Argument that, when it comes to God’s relationship to evil, Molinism is susceptible to the same liabilities as Calvinism. If his argument is successful, he has undercut, at least partially, justification for believing in Molinism. While I concede that Welty’s argument is successful in that it does undercut some justification for believing in Molinism, this concession does not entail that, as it relates to the problem of evil, the Calvinist and the Molinist are in the same epistemic position. In this article, I argue that, when it comes to God’s relationship to evil, the Molinist is in a superior epistemic situation to the Calvinist. I do this in two steps. First, I argue for what I call the Robust Felix Culpa Theodicy. Second, I argue that the Robust Felix Culpa Theodicy is incompatible with Calvinism.